Complication and revision rates after reverse total shoulder revision from hemiarthroplasty: a systematic review. (October 2022) - Reddy, Arjun K; Checketts, Jake X; Stephens, B Joshua; Anderson, J Michael; Cooper, Craig M; Hunt, Tyler; Fishbeck, Keith; Boose, Marshall; Detweiler, Byron; Chalkin, Brian; Norris, Brent L
Background: Thus, the purpose of the present study was to (1) characterize common postoperative complications and (2) quantify the rates of revision in patients undergoing hemiarthroplasty to reverse total shoulder arthroplasty revisional surgery. We hypothesize that hardware loosenings will be the most common complication to occur in the sample, with the humeral component being the most common loosening. Methods: This systematic review adhered to PRISMA reporting guideline. For our inclusion criteria, we included any study that contained intraoperative and/or postoperative complication data, and revision rates on patients who had undergone revision reverse total shoulder arthroplasty due to a failed hemiarthroplasty. Complications include neurologic injury, deep surgical site infections, hardware loosening/prosthetic instability, and postoperative fractures (acromion, glenoid, and humeral fractures). Results: The study contained 22 studies that assessed complications from shoulders that had revision reverse total shoulder arthroplasty from a hemiarthroplasty, with a total sample of 925 shoulders. We found that the most common complication to occur was hardware loosenings (5.3%), and of the hardware loosenings, humeral loosenings (3.8%) were the most common. The revision rate was found to be 10.7%. Conclusion: This systematic review found that revision reverse total shoulder arthroplasty for failed hemiarthroplasty has a high overall complication and reintervention rates, specifically for hardware loosening and revision rates.